High‐Throughput Chiral LC–MS/MS Method Using Overlapping Injection Mode for the Determination of Pantoprazole Enantiomers in Human Plasma with Application to Pharmacokinetic Study. Issue 7 (July 2016) - Li, Shengni; Jiang, Huafang; Wang, Yiya; Liu, Yinli; Shen, Xiaohang; Liang, Wenzhong; Hong, Zhanying
Abstract: A sensitive and high‐throughput chiral liquid chromatography–tandem mass spectrometry method was developed and validated for the quantification of R‐pantoprazole and S‐pantoprazole in human plasma. Sample extraction was carried out by using ethyl acetate liquid–liquid extraction in 96‐well plate format. The separation of pantoprazole enantiomers was performed on a CHIRALCEL OJ‐RH column and an overlapping injection mode was used to achieve a run time of 5.0 min/sample. The mobile phase consisted of 1) 10 mM ammonium acetate in methanol: acetonitrile (1:1, v/v) and 2) 20 mM ammonium acetate in water. Isocratic elution was used with flow rate at 500 μL/min. The enantiomers were quantified on a triple‐quadrupole mass spectrometer under multiple reaction monitoring (MRM) mode with m/z 382.1/230.0 for pantoprazole and m/z 388.4/230.1 for pantoprazole‐d7. Linearity from 20.0 to 5000 ng/mL was established for each enantiomer (r 2  > 0.99). Extraction recovery ranged from 91.7% to 96.4% for R‐pantoprazole and from 92.5% to 96.5% for S‐pantoprazole and the IS‐normalized matrix factor was 0.98 to 1.07 for R‐pantoprazole and S‐pantoprazole, respectively. The method was demonstrated with acceptable accuracy, precision, selectivity, and stability and the method was applied to support a pharmacokinetic study of a phase I clinical trial of racemic pantoprazole in healthy Chinese subjects. Chirality 28:569–575, 2016 . © 2016 Wiley Periodicals, Inc. Abstract :